2018
DOI: 10.3855/jidc.10126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of azithromycin vs doxycycline prophylaxis in leptospirosis, A randomized double blind placebo-controlled trial

Abstract: Introduction: Leptospirosis is an important zoonotic disease in paddy field with 29.5% prevalence rate in Mazandaran province and 4% to 52% mortality rate among hospitalized patients. Prevention is an important strategy for the control of this disease. This study aimed to compare the prophylactic effect of azithromycin versus doxycycline against leptospirosis in an endemic area in north of Iran. Methodology: In this randomized double-blind placebo-controlled trial, paddy field workers (n = 187) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Eight trials assessed prophylactic treatment against leptospirosis with different strategies: four of them with 200 mg of doxycycline weekly [ 24 , 26 , 28 , 30 ], two with daily oral penicillin [ 23 , 27 ], another two with a single dose of doxycycline at the time of exposure to flood water [ 25 , 29 ]. One of them also compared doxycycline prophylaxis with a weekly azithromycin regimen [ 30 ]. Among all these trials, they comprise 4905 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight trials assessed prophylactic treatment against leptospirosis with different strategies: four of them with 200 mg of doxycycline weekly [ 24 , 26 , 28 , 30 ], two with daily oral penicillin [ 23 , 27 ], another two with a single dose of doxycycline at the time of exposure to flood water [ 25 , 29 ]. One of them also compared doxycycline prophylaxis with a weekly azithromycin regimen [ 30 ]. Among all these trials, they comprise 4905 patients.…”
Section: Resultsmentioning
confidence: 99%
“…There was enormous heterogeneity among the studies. Two of them showed a clear benefit of doxycycline [ 24 , 28 ], but the most recent trial result did not show this benefit [ 30 ]. However, this study showed a lower percentage of new IgG seropositivity in those patients who received chemoprophylaxis than in the placebo group ( Table 3 ) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged elevation in serum bilirubin levels may not adequately reflect recovery of liver injury in this disease. ICG clearance appears to be a promising marker for the detection of hepatic dysfunction and recovery in icteric leptospirosis (66).…”
Section: Diagnostic Testsmentioning
confidence: 99%